Authorship Pattern and Collaborative Research in Aquaculture Journals - Ezhilrani, R.; Surianarayanan, S.; Kanthimathi, S. (Journal of Information and Knowledge, 2006)
An Investigation was made on the authorship pattern in Aquaculture Journals, based on the data collected from Aquatic Sciences and Fisheries Abstracts Part I (ASFA I) for a period of 3 years i.e. 1991, 1996 and 2001. In all the years, multiple authored contributions were more than that of single authors in all broad areas of aquaculture as the values of contributions of multiple authors ranged from 57.1% to 90.8 % in different aspects of Aquaculture. The degree of collaboration was found to be 0.85 for all the three years and it ranged from 0.83 (1991) to 0.86 (1996 and 2001).